Pelatihan untuk Pendidik Sekolah Menengah Kejuruan: Integrasi Kemampuan Numerasi pada Mata Pelajaran SMK: Pengabdian - Rica Wijayanti; Yusron, Rifky Maulana; Aldila Septiana; Zainudin, Zainudin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of holding this community service program is to provide training to subject teachers at Vocational High Schools (SMK) on the integration of numeracy skills in subjects taught at SMK. The method used to run this program is the direct talk show method between the resource persons and the participants of the training program. The results obtained from this activity are (1) the positive response from all participants to the program we hold; (2) response to the attractiveness of the presentation of material 84.44% in the very interesting category, 11.11% in the interesting category, and 4.45%; The response to benefits was 95% in the very useful category and 5% in the beneficial category. Another result that we obtained from this activity is an increase in knowledge about the integration of numeracy skills into several subjects in Vocational High Schools. This proves that teachers as the main figures in the world of education can be directly involved in helping the government in improving numeracy skills. Teachers can provide simple examples of students' life problems, so that students can directly apply their knowledge of numeracy. The habituation of students in solving problems about numeracy is also a driver to improve numeracy skills in the students themselves.